Low‐Light Shadow Imaging Using Quadrature‐Noise Detection with a Camera. Issue 7 (9th June 2022) - Cuozzo, Savannah L.; Barge, Pratik J.; Prajapati, Nikunjkumar; Bhusal, Narayan; Lee, Hwang; Cohen, Lior; Novikova, Irina; Mikhailov, Eugeniy E.
Abstract: This paper experimentally demonstrates an imaging technique based on quadrature noise modification after interaction with an opaque object. By using a homodyne‐like detection scheme, the detrimental effect of the camera dark noise is eliminated, making this approach particularly attractive for imaging scenarios which require weak illumination. As an example, the image of an object illuminated with a squeezed vacuum is reconstructed using a total of 800 probing photons, utilizing less than one photon per frame on average. Abstract : This paper experimentally demonstrates an imaging technique based on quadrature noise modification after interaction with an opaque object. By using a homodyne‐like detection scheme, the detrimental effect of the camera dark noise is eliminated, making this approach particularly attractive for imaging scenarios that require weak illumination.